THE EFFECT OF SAVING BEHAVIOR AND FINANCIAL LITERACY ON INVESTMENT DECISIONS IN THE GENERATION Z CAPITAL MARKET IN SURABAYA - Michaela, Olivia; Anastasia, Njo (Jurnal Ekonomi dan Manajemen, 2022)
Investment among young people shows rapid growth rates due to financial benefits. Saving activities are replaced by investing activities. This study explores the effect of saving behavior and financial literacy on investment decisions in the capital market by Generation Z in Surabaya. Data collection using a questionnaire distributed online to Generation Z aged 17-23 years who live in Surabaya and have invested in the capital market obtained as many as 100 respondents. The primary data was processed using SEM-PLS 3.0. The study results show that saving behavior and financial literacy significantly influence the investment decisions of Generation Z in the capital market. This research proves that there is a behavioral transition in Generation Z from a saving society to investing society. The implications of research for the government and capital market players through education are active investments to drive the economy, especially in the capital market and contribute to developing the State of Indonesia. However, Generation Z needs to be directed to seek information before investing to make the right decisions.